PENGELOLAAN SISTEM INFORMASI TERHADAP PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH (STUDI KASUS : SD MUHAMMADIYAH 2 SURAKARTA) - WIJIYANT0, WIJIYANT0 (2011)
The main focus of this research is "Characteristics of Management Information Systems in Principal Decision Making." The purpose of this study are 1) To describe the characteristics of Management Information Systems 2 SD Muhammadiyah Surakarta 2) Describe the supporting documents in Management Information Systems 2 SD Muhammadiyah Surakarta. 3) Describe the characteristics of the manual in Management Information Systems 2 SD Muhammadiyah Surakarta . This research was conducted at 2 SD Muhammadiyah Surakarta, using a qualitative approach. Data collection methods used are in-depth interviews, observation (observation) and documentation. Analysis using four stages which include data collection, data reduction, data presentation, and conclusion / verification. The validity of the data was done by using triangulation. The results (1) Characteristics of Management Information Systems in SD Muhammadiyah Surakarta consists of two components in the form of sub-systems hardware, software and human resources. The hardware is a system that has a sub- system CPU, device I / O and memory, the supra system hardware is a computer system. Limit system ie principal, teachers, staff and students. Environment outside the system comprises parent role, the role of Education, the role of schools, standardization, and education funding. Liaison ie transaction processing, control and strategic planning. Enter in the form of raw data from teachers, students and school finance. The output of output data. Processing of the process of changing raw data into a data base and target or goal that is fleksibilotas, accountability and transparency. (2) Characteristics of Management Information Systems Supporting the 2 SD Muhammadiyah Surakarta, among other data base systems in the form of connections and settings, student management, academic management, teachers and staff management, library management and reporting. Decission support system named as the principal consideration in making decisions. Information Resources Management is to provide information about student management, academic management, teacher management and employees, management perpustakaa. User Machine operating system, namely human resources management information system school. Synergic organization that is a synergistic cooperation between principals, teachers, staff and students in using management information systems. (3) Characteristics of Management Information System Manual at 2 SD Muhammadiyah Surakarta, which consists of human resource information systems, information systems academic, student information systems and E learning systems.